Hepacivirus NS3/4A Proteases Interfere with MAVS Signaling in both Their Cognate Animal Hosts and Humans: Implications for Zoonotic Transmission - Anggakusuma (J Virol, 2016)
Multiple novel members of the genus Hepacivirus have recently been discovered in diverse mammalian species. However, to date, their replication mechanisms and zoonotic potential have not been explored in detail. The NS3/4A serine protease of hepatitis C virus (HCV) is critical for cleavage of the viral polyprotein. It also cleaves the cellular innate immune adaptor MAVS, thus decreasing interferon (IFN) production and contributing to HCV persistence in the human host. To investigate the conservation of fundamental aspects of the hepaciviral life cycle, we explored if MAVS cleavage and suppression of innate immune signaling represent a common mechanism employed across different clades of the genus Hepacivirus to enhance viral replication. To estimate the zoonotic potential of these nonhuman hepaciviruses, we assessed if their NS3/4A proteases were capable of cleaving human MAVS. NS3/4A proteases of viruses infecting colobus monkeys, rodents, horses, and cows cleaved the MAVS proteins of their cognate hosts and interfered with the ability of MAVS to induce the IFN-β promoter. All NS3/4A proteases from nonhuman viruses readily cleaved human MAVS. Thus, NS3/4A-dependent cleavage of MAVS is a conserved replication strategy across multiple clades within the genus Hepacivirus. Human MAVS is susceptible to cleavage by these nonhuman viral proteases, indicating that it does not pose a barrier for zoonotic transmission of these viruses to humans. IMPORTANCE Virus infection is recognized by cellular sensor proteins triggering innate immune signaling and antiviral defenses. While viruses have evolved strategies to thwart these antiviral programs in their cognate host species, these evasion mechanisms are often ineffective in a novel host, thus limiting viral transmission across species. HCV, the best-characterized member of the genus Hepacivirus within the family Flaviviridae, uses its NS3/4A protease to disrupt innate immune signaling by cleaving the cellular adaptor protein MAVS. Recently, a large number of HCV-related viruses have been discovered in various animal species, including wild, livestock, and companion animals. We show that the NS3/4A proteases of these hepaciviruses from different animals and representing various clades of the genus cleave their cognate host MAVS proteins in addition to human MAVS. Therefore, cleavage of MAVS is a common strategy of hepaciviruses, and human MAVS is likely unable to limit replication of these nonhuman viruses upon zoonotic exposure.